Disentangling the Role of Linguistics in English Language Teaching - Kelik Wachyudi (ENGLISH EDUCATION DEPARTMENT - UNIVERSITAS SINGAPERBANGSA KARAWANG, 2019)
The research paper attempt to disentangle of (applied) linguistics in English language teaching. In this research, I used a literature review as my method. The result revealed that the role (applied) linguistics in English language teaching is needed for language learners. As a result, English language learners have beneficial from (applied) linguistics along with study English language teaching. The content of (applied) linguistics help language learners better to comprehend ELT.